2022
DOI: 10.1155/2022/2671343
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement of Cardiac and Endothelial Functions of Xue-Fu-Zhu-Yu Decoction for Patients with Acute Coronary Syndrome: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background. Xue-Fu-Zhu-Yu decoction (XFZYD) is a traditional Chinese prescription that has been used to treat patients with blood stasis in China for many years. The present study aimed to evaluate the improvement of cardiac and endothelial functions of XFZYD for patients with acute coronary syndrome (ACS) through a systematic review and meta-analysis. Methods. Six databases were searched to collect RCTs related to the treatment of XFZYD for ACS. The primary outcomes were cardiac and endothelial functions, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Two SRs/MAs [ 29 , 38 ] reported that XFZY was effective in reducing LDL-C (1 low-quality piece of evidence and 1 extremely low quality piece of evidence), TC (1 low-quality piece of evidence and 1 extremely low-quality piece of evidence), and one SR/MA [ 29 ] reported that XFZY was effective in increasing HDL-C (low-quality evidence). One SR/MA [ 30 ] reported that XFZY was effective in treating LVEF (low-quality evidence), LVESD (low-quality evidence), NO (extremely low-quality evidence), ET-1 (extremely low-quality evidence), ICAM-1 (extremely low-quality evidence), SOD (extremely low-quality evidence), MDA (extremely low-quality evidence), BNP (extremely low-quality evidence), and CK-MB (extremely low-quality evidence) in patients with CHD. In addition, the results of one SR/MA [ 27 ] showed significant efficacy of XFZY in the treatment of AF (low-quality evidence), DAP (low-quality evidence), WBV (low-quality evidence), PV (extremely low-quality evidence), FB (extremely low-quality evidence), NO (low-quality evidence), and ET-1 (low-quality evidence).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two SRs/MAs [ 29 , 38 ] reported that XFZY was effective in reducing LDL-C (1 low-quality piece of evidence and 1 extremely low quality piece of evidence), TC (1 low-quality piece of evidence and 1 extremely low-quality piece of evidence), and one SR/MA [ 29 ] reported that XFZY was effective in increasing HDL-C (low-quality evidence). One SR/MA [ 30 ] reported that XFZY was effective in treating LVEF (low-quality evidence), LVESD (low-quality evidence), NO (extremely low-quality evidence), ET-1 (extremely low-quality evidence), ICAM-1 (extremely low-quality evidence), SOD (extremely low-quality evidence), MDA (extremely low-quality evidence), BNP (extremely low-quality evidence), and CK-MB (extremely low-quality evidence) in patients with CHD. In addition, the results of one SR/MA [ 27 ] showed significant efficacy of XFZY in the treatment of AF (low-quality evidence), DAP (low-quality evidence), WBV (low-quality evidence), PV (extremely low-quality evidence), FB (extremely low-quality evidence), NO (low-quality evidence), and ET-1 (low-quality evidence).…”
Section: Resultsmentioning
confidence: 99%
“…One SR/MA [ 31 ] quantified the adverse events associated with XFZY for CHD treatment and showed no difference in the incidence of AEs (low-quality evidence) in XFZY compared to controls. In addition, nine SRs/MAs [ 29 , 30 , 32 – 36 , 38 , 39 ] gave a narrative description on the low incidence of adverse events in the XFZY group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Xuefu Zhuyu Decoction (XFZYD) has the effects of promoting blood circulation, eliminating blood stasis, activating vital energy to stop pain, and reinforcing functional activities of the heart, so it can greatly relieve angina pectoris after PCI. [ 18 , 19 ] XFZYD is a traditional classic soup for the treatment of chest paralysis, originated from the book “Yilin Gaicuo.” [ 20 ] Modern pharmacological analysis suggests that XFZYD can improve myocardial microcirculation perfusion and myocardial contractility, effectively inhibit platelet aggregation, dilate coronary arteries and peripheral vessels, prevent the formation of atherosclerosis, and ameliorate myocardial ischemia and hypoxia. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%